Effect of Dried Blood Spot Quality on Newborn Screening Analyte Concentrations and Recommendations for Minimum Acceptance Criteria for Sample Analysis. (6th January 2020) - George, Roanna S; Moat, Stuart J
Abstract: BACKGROUND: The analysis of dried blood spots has been used routinely for newborn screening since the early 1970s, and the number of disorders screened has expanded substantially in recent years. However, there is a lack of evidence regarding minimum blood spot quality acceptance criteria for sample analysis. METHODS: Blood pools were spiked with phenylalanine, tyrosine, leucine, methionine, octanoylcarnitine, decanoylcarnitine, isovalerylcarnitine, glutarylcarnitine, thyroid-stimulating hormone, and immunoreactive trypsinogen to concentrations at the analytical cutoffs used in UK screening protocols. We evaluated the effect of sample volume applied to the card (10, 20, 50, 75, and 100 μL), punch location (central vs peripheral), and sample quality (double layering, applying blood to both sides of the filter paper, multispotting, applying insufficient sample, and compressing the sample after application). RESULTS: Compression of blood spots produced significantly lower results (14%–44%) for all analytes measured ( P < 0.001). Smaller blood spots produced significantly lower results (15%–24% for 10-μL vs 50-μL sample size) for all analytes at all concentrations measured ( P < 0.001). Results obtained from peripheral punches were higher than those from a central punch, although this did not reach statistical significance for all analytes. Insufficient and multispotted samples demonstrated heterogeneous results. CONCLUSIONS: All blood spots containing ≤20 μL (blood spot diameter <8 mm), those in which blood has not fully penetrated the filter paper, and all samples with evidence of compression should be rejected, since there is a risk of producing false-negative results.